HUBUNGAN PENERAPAN PEDOMAN GIZI SEIMBANG DENGAN STATUS GIZI MAHASISWA PROGRAM STUDI S1 GIZI IKEST MUHAMMADIYAH PALEMBANG - Siti Soleha; Heri Shatriadi; Anjelina (jurnal kesehatan terapan sains dan teknologi, 2023)
Introduction: Nutritional status is a condition that is determined by the level of physical need for energy and nutrients obtained from food intake and has a measurable physical impact. Aim. Method: This research used descriptive analytic research, with a cross- sectional approach (a cross-sectional Study), and data collection was carried out simultaneously using a questionnaire that aimed to determine the relationship between balanced nutritional guidelines and nutritional status. Results: The results of the analysis showed that 28.1% of students had abnormal nutritional status, and 71.9% had normal nutritional status. There is a relationship between the habit of consuming various foods, namely energy intake (p = 0.034) and protein (0.008) and nutritional status, clean and healthy lifestyle with nutritional status (p=0.029); physical activity (p-0.01) with nutritional status, and normal weight monitoring (p-0.01) with nutritional status Discussion:There is a relationship between balanced nutrition guidelines and the nutritional status of nutrition students.